2020
DOI: 10.1002/fes3.234
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in rice seed germination via improved respiratory metabolism under chilling stress

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
(80 reference statements)
1
23
0
Order By: Relevance
“…e SA, ASA, and CaCl 2 primed seed showed high germination percentages and low MGT under low temperature stress conditions, similar to the studies in rice [26,27], corn [12,15,28], and S. miltiorrhiza [29]. Salicylic acid is an antioxidant that inhibits oxidative reactions, helps regulate cell growth (cell enlargement and division), and activates amino acids and proteins [30] that help protect the cell structure [31].…”
Section: Discussionsupporting
confidence: 75%
“…e SA, ASA, and CaCl 2 primed seed showed high germination percentages and low MGT under low temperature stress conditions, similar to the studies in rice [26,27], corn [12,15,28], and S. miltiorrhiza [29]. Salicylic acid is an antioxidant that inhibits oxidative reactions, helps regulate cell growth (cell enlargement and division), and activates amino acids and proteins [30] that help protect the cell structure [31].…”
Section: Discussionsupporting
confidence: 75%
“…In addition to starch degradation, several metabolic events were also reported to contribute to stronger chilling tolerance in primed seed. Our previous research found that the better germination ability in primed rice seed under chilling stress was associated with higher respiration rate (Wang et al 2016a ; b ), and such positive effect was attributed to the improved ATP levels, glycolysis metabolism and the repair and biogenesis of mitochondria in primed rice seeds (Nie et al 2020 ). Besides, the primed rice seeds obsessed lower MDA content and higher level of antioxidant capacity under abiotic stresses (Zheng et al 2016 ; Hussain et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The treatments were No-priming-Normal Temperature (NT); No priming-Chilling Stress (CK); Se priming-Chilling stress (Se) and SA priming-Chilling stress (SA). Previously, several studies have shown that the rice seed germination and seedling growth would be severely inhibited when germinated under the temperature of 16–20 °C (Yoshida 1981; Sipaseuth et al 2007; Wang et al 2016a ; Nie et al 2020 ). Therefore, the temperature for chilling stress was set as 16 °C, and the temperature for normal temperature treatment was set as 25 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations